Towards the co-production of fisheries knowledge for co-management using mobile technologies - Iversson Piazza, Tatiana (Department of Environmental and Geographical Science, 2017)
Fishing is an ancient way of food gathering, which has been instrumental for the healthy living of many people, for many years. Nowadays, fishing is particularly important to developing countries since the value of fish surpasses that of agricultural commodities such as sugar and rice. People living along the coast have been harvesting marine resources for basic subsistence for generations and at present several small-scale fisheries operate along the South African coastline, ranging from the shore-based harvesting of intertidal resources such as mussels, to the targeting of migratory line-fish stocks using small motorized vessels. Due to their high dependence on marine resource harvesting, small-scale fishers (SSF) are among the most vulnerable socio-economic groups, and while small-scale fisheries employ the vast majority of the world's fishers, they are often marginalized and ignored. The lack of appropriate governance in South African small-scale fisheries has made it hard for fishers to benefit from the resources that are readily available to them. However, changes within fisheries management practices have led to the move from conventional resource-centred strategies to management approaches that recognize the complexity of the sector. The new small-scale fisheries policy, currently in its implementation phase, embraces many of these new approaches but does not necessary prepare small-scale fishers to actively participate in the co-management of their resources. Furthermore, the lack of reliable data and information about small-scale fisheries, due to historical marginalisation, is currently one of the primary challenges facing the sector in the country, and preventing small-fishers from demonstrating to policy makers the potential of the sector to contribute towards food security and poverty eradication. The purpose of this study was to explore the potential of a mobile app in bringing about a co-production of fisheries knowledge and stimulating the co-management of fisheries, using the fishing communities of Lambertsbaai on the West Coast and Struisbaai along the South Coast as case studies. The research aimed to understand and assess the concerns and uncertainties of formalizing the mobile app (Abalobi) and explore if the mobile app can entice fishers' enthusiasm towards the implementation of